A Comparative Study on a Novel Fibula Malleolus Cap to Increase the Accuracy of Oncologic Jaw Reconstruction - Pu, Jingya Jane; Choi, Wing Shan; Yeung, Wai Kan; Yang, Wei-Fa; Zhu, Wang-Yong; Su, Yu-Xiong (Frontiers in Oncology, 2022)
Objectives Although computer-assisted surgery using fibula flap has been widely applied for oncologic jaw reconstruction in recent years, the inaccurate positioning of the fibula harvest guide brings sliding and rotational errors, which leads to compromised accuracy in simultaneous implant placement and dental rehabilitation. This study aimed to develop a novel three-dimensional (3D)-printed patient-specific fibula malleolus cap to increase oncologic reconstruction accuracy. Methods In this prospective comparative study with a recent historical control cohort, patients in need of oncologic jaw reconstruction with fibula free flaps were recruited. In the study group, the fibula was harvested with the guide of the malleolus cap, whereas in the control group, without the malleolus cap. Deviations of location and angulation of distal fibula osteotomies, jaw reconstruction segments, and simultaneous dental implants were compared. Results Twenty patients were recruited, with 10 in each arm. The application of the malleolus cap significantly reduced the deviations in locations and angles of distal fibula osteotomies, from 9.5 to 4.1 mm and 25.3° to 8.7°. For the simultaneous dental implants placed in the fibula flaps, there was a significant increase in the accuracy of implant platform locations (the average deviation from 3.2 to 1.3 mm), apex locations (from 3.8 to 1.5 mm), and angles (from 11.3° to 4.6°). No significant difference was detected in the accuracy of fibula reconstruction segments. Conclusions We developed a novel fibula malleolus cap to overcome the sliding and rotational errors during fibula flap harvesting for oncologic jaw reconstruction, with increased accuracy in simultaneous dental implants. This is a step forward to achieve a satisfactory functional outcome of jaw reconstruction with dental rehabilitation.